“That the Kingdom Commands the King: and not the King to the Kingdom”. The Legitimacy of Charles the First at the Time of the Communities of Castile Five Hundred Years Later (Res Publica. Revista de Historia de las Ideas Políticas, 2020)
The Comunidades was a political and social movement which development from May 1520 to April 1521 in Castile. The leaders of this movement were able to raise fourteen cities against the politics of Charles I, future Emperor Charles V, and his collaborators. The article is built by selecting three historical facts that led to discussion between the comuneros and followers of Emperor Charles. Three political concepts were discussed during this period: monarchical legitimacy, political representation and agreed monarchy. The fundamental question was to determine what institution had preeminence the king or the kingdom through its representatives.